(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2026)
This paper investigates the long-term effects of trade liberalization on innovation in developing economies during the Great Liberalization period (1980–1992). Using a two-way fixed effects model and the Sachs et al. (1995) classification, several innovation proxies are analyzed, including patents, industrial applications, R&D expenditure, and labor productivity. By separately examining patents filed by residents and non-residents, genuine domestic innovation responses are distinguished from the formal registration effects induced by the contemporaneous TRIPS Agreement. The results demonstrate that trade liberalization significantly increases innovation outcomes, with robust patterns for total patents and industrial applications, more mixed evidence for R&D expenditure and labor productivity, and dynamic effects persisting for up to 30 years. Foreign competition, measured through foreign direct investment (FDI), emerges as a key transmission channel, stimulating technological advancements and industrial applications. Policymakers should consider the long-term benefits of trade openness, despite short-term adjustment costs, while fostering absorptive capacity to maximize knowledge spillovers.